Lettere d’artista : invenzione di un patrimonio nell’Italia del nation-building - Laganà, Annalisa (Clio. Saggi di scienze storiche, archeologiche e storico-artistiche, 2024)
The book describes the shaping and institutionalisation of a part of Italy’s cultural heritage during nation-building, from the emergence of cultural nationalism at the beginning of the 18th century to the Fascist period. The research aims to draft the first history of artists’ letters patrimonialisation, by reconstructing the history of collections, musealisations and editions of this peculiar source for art history, which was subject to conservation policies after Italy’s unification. This essay addresses many issues in the field of artistic epistolography and it outlines how the historical and identity value of these archives originated.